2016
DOI: 10.18632/oncotarget.9202
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling MYCN regulatory networks in neuroblastoma via integrative analysis of heterogeneous genomics data

Abstract: MYCN, an oncogenic transcription factor of the Myc family, is a major driver of neuroblastoma tumorigenesis. Due to the difficulty in drugging MYCN directly, revealing the molecules in MYCN regulatory networks will help to identify effective therapeutic targets for neuroblastoma therapy. Here we perform ChIP-sequencing and small RNA-sequencing of neuroblastoma cells to determine the MYCN-binding sites and MYCN-associated microRNAs, and integrate various types of genomic data to construct MYCN regulatory networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 102 publications
(106 reference statements)
6
34
1
Order By: Relevance
“…2e ), indicating that TFAP4 is directly regulated by MYCN. Consistent with our results, Hsu et al [ 26 ], performed ChIP-seq using an anti-MYCN antibody in the MYCN-amplified neuroblastoma cell BE(2)C, demonstrated that TFAP4 is a direct transcriptional MYCN target.…”
Section: Resultssupporting
confidence: 93%
“…2e ), indicating that TFAP4 is directly regulated by MYCN. Consistent with our results, Hsu et al [ 26 ], performed ChIP-seq using an anti-MYCN antibody in the MYCN-amplified neuroblastoma cell BE(2)C, demonstrated that TFAP4 is a direct transcriptional MYCN target.…”
Section: Resultssupporting
confidence: 93%
“…This suggests that SNHG1 is not only correlated with MYCN amplification but also with MYCN expression. Moreover, our ChIP-seq data analysis observed MYCN binding sites in the promoter of SNHG1 ( Supplementary Figure S5 ) [ 33 ]. Furthermore, previous study has pointed out that lncRNAs possess tissue-specific expression [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…How to integrate and mine these data is an important issue. 4 There is no doubt that bioinformatics or computational biology can help researchers analyze these big omics data. The categories of bioinformatics contain many subfields such as sequence analysis, genome annotation, transcriptome and proteome analyses, as well as network biology and dynamic modeling.…”
Section: Bioinformaticsmentioning
confidence: 99%
“…[7][8][9][10] In addition to target and drug discovery, cancer systems biology represents a valuable contribution to efforts toward understanding the molecular mechanism of drugs in various cancer types 5,11 and regulation in cancer progression. 4 …”
Section: Systems Biology In Cancer Researchmentioning
confidence: 99%
See 1 more Smart Citation